Comparative Study on Fetomaternal Outcome after Lower Uterine Segment Caesarean Section and Vaginal Delivery in Eclamptic Patient - Khandoker, Monika; Joy, Swapna Biswas; Das, Sanjoy Kumar; Biswas, Ananta Kumar (Faridpur Medical College Journal, 2020)
Eclampsia has a high prevalence in our country with a high mortality rate. Eclampsia is uniquely a disease of pregnancy and regardless of gestational age. It is recognized that termination of pregnancy is the only definitive care of pathophysiological event in eclampsia. This study was done to observe fetomaternal outcome in Lower Uterine Segment Caesarean Section (LUCS) and vaginal delivery in eclamptic patient. This cross sectional analytical study was carried out in eclampsia department of Obst and Gyane in Dhaka Medical College Hospital from July 2016 to June 2018. A uniform protocol was followed in all cases to have appropriate history, physical findings and laboratory investigations. In this study 98.0% patients were conscious on admission in group I and 96.0% in group II. This study showed significant difference in recurrence of convulsion after delivery between two groups. Recurrence of convulsion was 30% in vaginal delivery group and 6% in the cesarean section group. Total complications were found in 46.0% and 16.0% patients in group I and group II respectively in this study. The difference was statistically significant (p<0.05) between two groups. In this study PPH was the most common complication in both the groups. Abruptio placenta was found more common among the vaginal delivery group. On the other hand, electrolyte imbalance was found more in cesarean section group. Maternal death was only 2% and 1% in group I and group II respectively. In this study live birth was found 64.0% and 79% in group I and group II respectively. Asphyxia was more in neonates in group I than group II which was statistically significant. Referral of asphyxiated babies to NICU was found 63.0% and 56.0% in group I and II respectively. The difference was statistically not significant between two groups. Faridpur Med. Coll. J. Jan 2020;15(1): 16-20